2021
DOI: 10.1088/1757-899x/1046/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes and fracture resistance of nano-crystalline monolithic zirconia restorations upon aging

Abstract: To assess the effect of nano-modification of two CAD/CAM monolithic Zirconia systems (wet and dry-milled) on microstructural changes and fracture resistance upon aging. Twenty monolithic Zirconia discs (10mm x1.5mm) were divided into 2 groups (n=10) according to fabrication system;wet-milled (Incoris TZI) and dry-milled (CeramillZolid). Each group was subdivided into two subgroups (n=5), whether subjected to aging or not. Aging proceduresincluded accelerated hydrothermal aging and cyclic loading. Microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…to Kamel et al 18 They found that after aging procedure in wet milling system, peaks of monoclinic phase appeared significantly. While, minimal peaks of monoclinic phase appeared in dry milling system.…”
Section: Asdj Ain Shams Dental Journalmentioning
confidence: 88%
“…to Kamel et al 18 They found that after aging procedure in wet milling system, peaks of monoclinic phase appeared significantly. While, minimal peaks of monoclinic phase appeared in dry milling system.…”
Section: Asdj Ain Shams Dental Journalmentioning
confidence: 88%
“…These volumetric changes may affect the fit of zirconia crowns, especially when constructed over reverse-tapered preparation. 9 Die printing was accomplished by the Halot 3D Sky printer. The printer has a resolution accuracy of 0.034mm and XY axis accuracy of 0.05mm, making it capable of providing high quality dies with high precision.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the process of sintering of zirconia after milling results in shrinkage rates of 30% for zirconia, which affects the accuracy of fit of Zirconia restorations. 9,10 One of the factors which affects the internal fit of the fixed restorations is the preparation angle. 11 The term 'angulation' refers to the angle of preparation or to the total occlusal convergence (TOC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 To simulate further of oral conditions, samples were subjected to accelerated hydrothermal aging. 56 Standardization of aging procedure was done according to standard aging protocol of ISO13356 by autoclaving zirconia samples of both groups at temperature of 134 o C and 2 bar pressure for 5 hours simulating 15 years serviceability. 57 This strategy was in accordance with another studies that mentioned the reliability of using autoclave to simulate oral conditions.…”
mentioning
confidence: 99%